Comparison between manual salting-out and commercialized DNA extraction from small volume of peripheral blood - Mohammad, Salina; Abdullah, Nor Zamzila; Ku Zaifah, Norsidah; Farid Wajidi, Mustafa Fadzil; A. Talib, Norlelawati (Malaysian Society of Applied Biology, 2010)

(untitled)
The techniques of isolation deoxyribonucleic acid (DNA), a crucial step in the process of DNA analysis has progressed rapidly. The manual techniques for DNA purification have been gradually replaced by automation and purification kits. Although expensive, these commercialized techniques are prefered as they are superior in extracting DNA from small volumes of samples. These methods are also safer and rapid. The purpose of this study was to adopt and optimize the manual saltingout procedure for the purification of DNA from small volumes of blood, and to compare the cost of performing the technique to that of the Mini QIAmp DNA extraction kit (Qiagen) and fully automated technique Magtration 12C, Precision). Apart from being relatively safe and cheaper, we found that the optimized salting-out procedure was able to extract DNA that is comparable in quantity and quality from small volumes of blood.